Forward and Reverse shear transfer in beech LVL-concrete composites with singly inclined coach screw connectors. (15th November 2018) - Sebastian, W.M.; Piazza, M.; Harvey, Tristan; Webster, Tom
Highlights: Two-way shear tests on beech LVL-concrete connections with singly inclined screws. 45° tension and compression screw connections of high strength and ductility. 90° screws enable similar strength/modulus to 45° tension/compression screws. Repeat tests show good consistency of failure load, much less so of slip modulus. Gamma method shows sensitivity to the connection of uncracked depth and deflection. Abstract: Double-shear tests are reported on beech LVL-concrete composite connections based on coach screw connectors singly inclined at either 45° or 90°. On different specimens with the same screw orientation the longitudinal shear force was applied either in forward or reverse, because in practice concrete shrinkage, moisture-induced timber expansion and oscillatory (e.g. seismic) or moving loads can induce reversal of the force on the connection. The test data show that relative to the 90° screw connections, sloping the screws to 45° in tension only marginally affected longitudinal shear strength but led to a fivefold increase of slip modulus and to a significant drop in ductility, while sloping the screws the other way to 45° in compression only marginally affected slip modulus but led to an almost fourfold drop in longitudinal shear strength and to a substantial increase in ductility. The specimens tested within each group showed good consistency of shear strength and (except the 45° tension screw specimens, despite their consistent strengths) of failure mode, but high variability of slip modulus. Comparisons with previously tested timber-concrete composite (TCC) connections based on other screw types and layouts suggest good performance of the present connections. The gamma method applied to a given TCC T-section under load shows that the present alternate connections lead to quite different depths of uncracked concrete and so to significant variation of midspan deflection. In closing, it is recommended that both forward and reverse shear testing becomes a protocol for singly inclined coach screw-based TCC connections.